2022
DOI: 10.1002/uog.24754
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and ultrasound fusion technique in gynecology

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…US is a safe, non-invasive, real-time, and cost-effective clinical imaging modality that can be applied to image tissues deep within the body. It is one of the most widely used imaging modalities for the detection and diagnosis of disease, with applications including fetal [70] , [71] , genito-urinal [72] , [73] , cardiovascular [74] , [75] , [76] , orthopaedic [77] , [78] , breast [79] , [80] , [81] , and abdominal imaging [82] . US is also applied as a screening tool for early cancer detection due to its ability to differentiate cysts from solid masses based on target size, shape, and relative echogenicity [83] , [84] .…”
Section: Ultrasound Probes For In-vivo Imagingmentioning
confidence: 99%
“…US is a safe, non-invasive, real-time, and cost-effective clinical imaging modality that can be applied to image tissues deep within the body. It is one of the most widely used imaging modalities for the detection and diagnosis of disease, with applications including fetal [70] , [71] , genito-urinal [72] , [73] , cardiovascular [74] , [75] , [76] , orthopaedic [77] , [78] , breast [79] , [80] , [81] , and abdominal imaging [82] . US is also applied as a screening tool for early cancer detection due to its ability to differentiate cysts from solid masses based on target size, shape, and relative echogenicity [83] , [84] .…”
Section: Ultrasound Probes For In-vivo Imagingmentioning
confidence: 99%
“…Among the recent advances in imaging, the MRI/TVUS fusion technique is a new non-invasive diagnostic tool that could be useful in clinical practice because it may allow for improving the TVUS detection of some abnormalities using MRI and vice versa [ 86 ]. There is no consensus on the optimal requirements because of the limited number of published works about this technique [ 86 ]. In obstetrics and gynecology, preliminary studies suggested the potential value of fusion imaging techniques in diseases, such as DE, as well as scars from cesarean sections and gynecological cancers [ 86 ].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…There is no consensus on the optimal requirements because of the limited number of published works about this technique [ 86 ]. In obstetrics and gynecology, preliminary studies suggested the potential value of fusion imaging techniques in diseases, such as DE, as well as scars from cesarean sections and gynecological cancers [ 86 ]. Fusion imaging allows for the superimposition of the MRI and US images, providing real-time imaging capabilities and high tissue contrast [ 87 ].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a growing interest in offline fusion imaging, which refers to a-posteriori merging of two different imaging modalities [4][5][6][7][8][9] . We aimed to merge two 3D ultrasound volumes to create a single complete dataset of the entire brain in three orthogonal planes with consistent quality and spatial resolution throughout, allowing exploration of the central nervous system anatomy.…”
mentioning
confidence: 99%